Biobased poly(ethylene furanoate-co-ethylene succinate) copolyesters: solid state structure, melting point depression and biodegradability. Issue 87 (5th September 2016) - Terzopoulou, Zoe; Tsanaktsis, Vasilios; Bikiaris, Dimitrios N.; Exarhopoulos, Stylianos; Papageorgiou, Dimitrios G.; Papageorgiou, George Z.
Abstract : Novel, biobased poly(ethylene furanoate- co -ethylene succinate) copolyesters were successfully prepared by melt polycondensation and their solid state structure, melting point depression and biodegradability were evaluated in detail. Abstract : Poly(ethylene furanoate) (PEF) is a fully bio-based polyester with unique gas barrier properties, considered an alternative to poly(ethylene terephthalate) (PET) in food packaging applications. However, it is not biodegradable. For this reason, copolymerization with an aliphatic succinic acid monomer was investigated. The respective poly(ethylene furanoate- co -ethylene succinate) (PEFSu) copolymers were prepared via melt polycondensation from 2, 5-dimethylfuran-dicarboxylate, succinic acid and ethylene glycol at different ratios. 1 HNMR spectroscopy showed the copolymers are random. The crystallization and melting of the copolymers were thoroughly evaluated. Isodimorphic cocrystallization was concluded from both the WAXD patterns and the minimum in the plots of melting temperature versus composition. The pseudo-eutectic melting point corresponded to an ethylene succinate content of about 30 mol%. The enzymatic hydrolysis tests using Rhizopus delemar and Pseudomonas cepacia lipase revealed that the copolymers with up to 50 mol% ES units show measurable weight loss rates. For higher ES content, the copolymers showed fast hydrolysis.